Development of Employee Online Attendance System using Webcams and Web-Based Location (Case Study of CV. OTW Computer Gusaha) - Bagus Ramdana Kurnia Aji; M Mahaputra Hidayat; Alifia Julianti; Ahmad Arif Muzzani (Fakultas Teknik Universitas Bhayangkara, 2023)
Attendance is an activity of data collection to determine the number of people present at an activity in an institution or company. In the previous era, attendance at CV. OTW Computer Gusaha was still done manually through paper, which was very ineffective and inefficient, resulting in attendance data not being well stored. To solve this problem, a reliable and efficient online attendance application is needed for users. The purpose of this application is to improve the efficiency of the attendance process, facilitate monitoring and evaluation, and minimize the risk of fraud in the attendance process. The method used is the geolocation method. The results of this research show that an online attendance system using a webcam and a web-based location can improve the efficiency of CV. OTW Computer Gusaha and increase the discipline and responsibility of employees.